Homeland Conflict and Identity for Palestinian and Jewish Israeli Americans. - Weinzimmer, Julianne Melissa, 1978- (New Americans (LFB Scholarly Publishing LLC), 2011)
Weinzimmer examines various ways that homeland conflict affects the diasporic identities of first and second generation Jewish Israeli Americans and Palestinian Americans. Her work builds upon central tenets of conflict theory, collective memory and transnationalism literature, and narrative methodologies. Perceptions of homeland conflict are analyzed from multiple sources: past experiences; family stories; group-level accounts; media coverage; and homeland contacts. Homeland conflict proves to be a constitutive element of identity for both generations within each group, with differences obser.